Results of Development and Application of an Objective Structured Clinical Examination: A Pioneering Experience in Pharmaceutical Care - Zarzuelo, Maria Jose; Valverde-Merino, Maria Isabel; Fernandez-Rodriguez, Maria; Amador-Fernandez, Noelia; Uribe-Sanchez, Alberto; Gomez-Guzman, Manuel; Martinez-Martinez, Fernando (Indian Journal of Pharmaceutical Education and Research, 2021)
Objectives: Objective Structured Clinical Examination (OSCE) is a tool to assess skills and competencies and it can be relevant in Pharmacy studies and more specifically in Pharmaceutical Care (PC) to develop more practical and useful skills in the working life of a healthcare professional. Design and Methods: A prospective study was performed by students of the subject of PC in the Bachelor of Pharmacy and by students from the Master in PC, at the end of their classes. Five stations with standardized patients and written records were designed. A checklist was prepared in each station with various components to evaluate competencies and a questionnaire to explore students´ opinion was designed. Results: The mean of the global punctuation was 65.17±11.30/100, being higher for the Master student than Bachelor. 85.10% of students passed the exam. The best scored station by the students was the one of “Adherence” and the worst were both the written stations (“Dispensing Record” and “Medication Review Follow-up”). The best competency was technique. The activity was valued very positively according to the global score of the opinion questionnaire (4.50±0.50/5). Conclusion: Pharmacists must boost their skills and abilities required to perform pharmacy services. The use of OSCE represents a new tool to encourage and evaluate these PC skills.
Keywords: Competencies; Education; Objective Structured Clinical Evaluation; Pharmaceutical care; Pharmacy services